Time will tell: Decision making in premanifest and manifest Huntington’s disease - Heim, Beatrice (Brain Behav, 2020)
OBJECTIVE: To investigate cognitive flexibility in premanifest and manifest Huntington's disease (HD). BACKGROUND: HD is an autosomal dominant neurodegenerative disease characterized by motor, cognitive, and behavioral abnormalities with typical motor symptoms. In this study, we wanted to assess decision making in premanifest (pre‐HD) and manifest HD patients. METHODS: A total of 77 non‐demented subjects including 29 pre‐HD, 22 manifest HD patients, and 26 healthy controls (HC) were included. We stratified the pre‐HD group based on their estimated years to disease onset into a far (FAR, n = 13) and a near (NEAR, n = 16) group. Furthermore, participants performed the Montreal cognitive assessment battery (MoCA), the trail making task part A and B (TMT A, TMT B), the Symbol digit modalities test (SDMT), and the beads task. RESULTS: In the beads task, HD patients gathered less information than all other groups (all p‐values < .001). Furthermore, the NEAR group gathered less information than the FAR group (p < .001) and HC (p = .001). There was no difference between the HC and the FAR group (p = 1.0). In the TMT and the SDMT, HD patients were slower than all other groups (all p‐values < .01) but there were no other significant differences. CONCLUSIONS: Decision making with a higher degree of uncertainty may be an early neuropsychological sign to indicate the disease process prior to reaching criteria for motor diagnosis of HD.